Pengaruh Doping Ion Alumunium pada Kurva Serapan FTIR dan Struktur Kristal Nanopartikel Kobalt Ferit Hasil Kopresipitasi: Anisa Khoiriah, Utari, Budi Purnama - Anisa Khoiriah Anisa Khoiriah; Utari Utari; Budi Purnama Budi Purnama (Jurnal Fisika dan Aplikasinya, 2017)
It has been studied the aluminum doping effect on co-precipitated cobalt ferrite nanoparticles. Aluminum ion .was chosen considering covalent radius comparable to the radius of cobalt. The analysis of FTIR results showed that the change of constant force without and with doping aluminum ion on tetrahedral site was 0.23 N / m. The calculated of crystallite size from the strongest peak of XRD pattern indicated that the crystallite size reduces from 57.75 to 46.20 nm after doped aluminum. The change of the crystallite size was presumably due to the substitution of cobalt ions with aluminum ions since the aluminum covalent radius was smaller than cobalt ions.